Methods for management of soilborne plant pathogens - Mihajlović, Milica V.; Rekanović, Emil; Hrustić, Jovana; Grahovac, Mila; Tanović, Brankica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Soilborne pathogens cause significant economic losses in agricultural production all over the world. These species can survive for many years in the absence of a host plant by forming persistent structures such as microsclerotia, sclerotia, chlamydospores or oospores. Consequently, soilborne diseases are particularly difficult to predict, detect, diagnose and successfully control. Over the past 30 years, a fumigant, methyl bromide, has been widely used for their control in many crops. In 1992, methyl bromide was listed as an ozone-depleting substance under the Montreal Protocol − an international treaty to protect the ozone layer. During the phaseout of methyl bromide, problems generated in agricultural production made it clear that dependence on a single method or a single chemical should be avoided. The objective of this review paper was to summarize the current knowledge about different methods of soilborne disease control including: crop rotation, steam soil disinfection, soil amendments, hydroponics and soilless growing systems, soil solarization, grafting, biological control and use of natural compounds, and chemical control. Positive and negative aspects of all available methods were reviewed. Benefits, achieved by simultaneous application of several methods based on different mechanisms of actions, are discussed.